Uji Efektivitas Pupuk Amagro-S terhadap Pertumbuhan dan Hasil Padi (Oryza Sativa L.) pada Tanah Sawah Mineral Masam Lampung Timur - Soelaeman, Y. (Politeknik Negeri Lampung., 2010)
Effectiveness studies of solid organic fertilizer/bulk amagro-S has been done at the Garden Experiment/KP Tamanbogo, East Lapung MH 2008. Treatment of the test are: 1). Control, 2). Without fertilizer dose of NPK + Amagro-1 S, 3). Standard NPK fertilizer (250 kg / ha urea + 100 kg.ha KCI)+without amogro-S, 4). Standard PK fertilizer (100 kg. ha SP 36 + 100 kg / ha-1KCI) dose AMOGRO ½-s, 5). Standard PK fertilizer+¾ Amogro_S dose, 6). Standard PK fertilizer + 1 dose Amogro-S, 7). Standard PK fertilizer +1 ¼ Amagro dose-S and 8).Standard PK fertilizer dose of 1 ½ Amagro-S. Research design using a randomized block design with 3 replications. The results showed that the fertilizer-S amagro meet the quality requirements that have been established as a solid organic fertilizer. Fertilization amagro=S at a dose of 2000-6000 kg. Ha-1 with P and K in high doses to plant standards, the number of seedling weight and 1000 grain harvest of dry grain weight (GKP) is not significantly different in nominal terms even better compared with the dose of fertilizer N, P and K standards. Dry grain harvest Hasik / GKP highest (5.850 t / ha) achieved by the treatment of 4000 kg.ha-1Amagro-S disetai with P and K fertilizer at standard doses. Fertilization Amagro-S from 2000 to 6000 kg.ha-1along with P and K fertilizer at standard doses can increase the Relative Agronomic Effectiveness (RAE) between 18,40-69,33% higher. While the use of fertilizer Amagro-S at a dose of 4000 kg / ha of fertilizer without P only gives rise RAE of 3.99%. Solid organic fertilizer / bulk Amagri-S can be used for paddy rice, but the monitoring needs to be done soil properties on the usage of fertilizer-S Amagro long term. Keywords: Effectiveness, Amagro-S fertilizer, rice paddy